Perancangan Antena Mikrostrip Mimo 5g Dalam Peningkatan Gain Untuk Aplikasi Base Station - Muhammad Saiful Fadhil Reyhan; Yusnita Rahayu; Adit Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The last decade has been enormous invasion of wireless device in the evolution of technology. The requirement of high throughput is needed to provide the quality of device such as audio, data, video, and games. However, the connected devices grown and increase critcially year by year. Multiple Input Multiple Output (MIMO) that has been embedded for 4G technologies as the one of technology is more likely adapted on 5G to improve the data peak rate for SNR(Signal-to-Noise Ratio). High gain and better efficency are needed for Base Station as transmit the power to receiver or connected device. MIMO can be confirmed as the solution to increase the gain with better effeciency. This paper proposed the design of MIMO antenna with high gain. The proposed antenna is designed RT Duroid 5880 substrate with the overall size of 136.5x40x0.127 mm3. The MIMO consist of 20 element antenna that achieved 26.4 dBi of gain at 38 GHz frequency and 22.2 dBi at 28GHz. Keyword: MIMO, 5G, High Gain, Base Station, Microstrip.